Static and dynamic impact of HVDC, TNB-EGAT interconnection system - Shahida, Mohd Said @ Sayed (2010)
HVDC interconnection TNB-EGAT system is the second stage of the grid interconnection between Malaysia and Thailand. This system is to export the electrical power during lower demand and import during TNB’s peak load. The objectives of this project are to study the static and dynamic impacts of HVDC TNB-EGAT system. This study will also focus on modeling and simulating of the HVDC interconnection system by using Power System Computer Aided Design (PSCAD/EMTDC) software. The load flow analysis has been conducted by comparing the simulation from PSCAD with the actual data. Hence, the fault analysis also has been conducted by locating the fault at the HVDC modeling which is the DC line fault analysis and AC signal phase short circuit at inverter station analysis. This system is stabilized by having a transient stability analysis. The PSCAD software has the features that can be used to conduct such analysis. This analysis has been performed and the impacts have been monitored on the system and both power system utilities. From the analysis, some improvements have been suggested for the future system